Problem-based scaffolding for prospective mathematics teachers in graph theory course - Wulandari, Yunita Oktavia; Khasanah, Fitria; Yuniarto, Eko (International Journal of Trends in Mathematics Education Research, 2023)
This study aimed to give a scaffolding process to improve the preservice teachers' ability in graph theory class. The present study implemented scaffolding techniques by administering graph theory questions. Four scaffoldings are used: (1) questioning, (2) prompting, (3) cueing, and (4) direct explanation. The choice of this problem can be observed through students' comprehension of graph theory. This research indicates that problem-based scaffolding can benefit students with challenges understanding graph theory. The students exhibit enthusiasm as they explore the interconnection between road systems, predatory and isomer, employing graph theory.